المخاوف الشائعة لدى أطفال الرياض - نحيلي, علي; زوبي, سليمة (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
هدف البحث إلى التعرف إلى: أنواع المخاوف الشائعة لدى أطفال الرياض وتكمـــن أهمية الموضوع في الكشف المبـــكر لمخاوف الأطفال. وقد اختيرت عينة مسحوبة عشوائياُ بلغ عددها(279) طفلا وطفلة. وأعدت الباحثة (مقياس مشكلة الخوف لدى أطفال الرياض) بوصفه أداة لجمع المعلومات عن طريق الأمهات . وأظهرت النتائج أن أكثر المخاوف شيوعاً لدى أطفال الرياض هي: الخوف من المجهول81% ويليه الخوف من الثعابين 53% ويليه الخوف من التصرف الخاطئ (41%) ثم الخوف من الأشباح (40%) والخوف من الظلام (39%). كما وجدت النتائج وجود فروق ذات دلالة إحصائية عند مستوى دلالة 0.01 بين متوسطات درجات الذكور ومتوسطات درجات الإناث في الخوف من المجهول، الخوف من الظلام والخوف من الثعابين، وذلك لمصلحة الذكور. بالإضافة إلى وجود فروق ذات دلالة إحصائية عند مستوى دلالة 0.01 بين متوسط درجات الذكور ومتوسط درجات الإناث في الخوف من الأشباح وذلك لمصلحة الإناث. وكذلك عدم وجود فروق ذات دلالة إحصائية عند مستوى دلالة 0.01 بين متوسط درجات الذكور ومتوسط درجات الإناث في الخوف من التصرف الخاطئ. This research aims to identify the types of concerns common to kindergarten children, and its significance lies in the early detection of children's fears, preventing the effects of fear in early childhood years from having a negative impact on the compatibility and efficiency of the individual in childhood. This study highlights the importance of early diagnosis for fear, relying on the factors associated with fear in children and the differences between males and females. The results obtained show that there are statistically significant differences (0.01) between male and female average scores in the question of fearing the unknown, the dark, and snakes, in favour of males. In addition, there are statistically significant differences (0.01) between male and female average scores in the case of fearing ghosts, in favour of females. The results also show no statistically significant differences at 0.01 between male and female average scores when it comes to fearing of wrong behaviour.